Implementasi Pembelajaran Nahwu Berbasis Al-Qur’an Dalam Meningkatkan Pemahaman Santri pada Materi Isim jamak di Pondok Pesantren Al-Luthfi Lolanan - Mokoagow, Chofifah; Rivai, Alimudin; Jamal, Misbahuddin (Program Studi Bahasa Arab, FTIK IAIN Manado, 2023)
In this study, researchers conducted an investigation to find a model for implementing Al-Qur'an-Based Nahwu Learning in Improving Santri's Understanding of Isim Jamak Material at Al-Luthfi Lolanan Islamic Boarding School by conducting a study through the stages of learning starting from (1) Learning planning Al-Qur'an-based Nahwu on Isim Jamak material at the Al-Luthfi Lolanan Islamic Boarding School is formulated by providing Isim Jamak materials in reference books such as Matan al-Jurumiyah, and al-Miftah, (2) Implementation of Al-Qur'an-based Nahwu learning -The Qur'an on plural noun material at the Al-Luthfi Lolanan Islamic Boarding School uses the deductive method with memorization models, lectures, field practice and Isim Jamak analysis through examples in the Qur'an. (3) Evaluation of Al-Qur'an-based Nahwu learning on Isim Jamak material at the Al-Luthfi Lolanan Islamic Boarding School uses two test models, namely oral and written.